High School Students Differentiated teaching on self-directed learning guidance - Phuong-Thuy Kieu, Chi-Trung Nguyen (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Self-directed learning (SDL) capacity is one of the core common values of students, as defined in the Vietnam General Education Curriculum 2018 (VGEC). Because of the students’ variety in capacity and needs, educators are challenged to assist in the development of self-directed learning skills and to encourage learners to more freely use self-direction in their learning activities by personalization and differentiation in teaching practices. However, previous works on SDL in Informatics for Vietnamese students mainly focus on educators’ teaching without considering academic diversity. Our work introduces differentiated teaching and criteria to classify students in Informatics. On the basis of criteria, we designed a procedure to develop SDL capacity in Informatics for high school students. We applied our method and examined the results by assess the perceptions of self-directed learning on 147 students from 5 provinces nationwide. The SDL capacity assessment shows that our differentiated teaching method provides an improvement on students’ SDL capacity scores, particularly the male students and the students living in rural areas.